2015
DOI: 10.1007/s00170-015-7357-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of ultrasonic-assisted friction stir process effect on in situ dispersion of multi-walled carbon nanotubes throughout polyamide 6

Abstract: The present article offers a modified method of friction stir process combined with ultrasonic vibrations in order to reinforce polyamide 6 (PA 6) using multi-walled carbon nanotubes (MWCNT). For this purpose, ultrasonicassisted friction stir process and simple friction stir process were performed to distribute the MWCNT particles among the PA 6. Field emission type of scanning electron microscopy, X-ray diffraction, Vickers' micro-hardness, and visual inspection were used to evaluate and compare properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…When it comes to connecting thermoplastics, ultrasonic welding has been shown to be a viable option among all of the fusion methods tested. The intermolecular interaction between the thermoplastics induced by ultrasonic vibrations causes intermolecular diffusion and trapping of the molecular chain within the liquid state on the interfaces of the weld polymer in this approach, which is a distinguishing property [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to connecting thermoplastics, ultrasonic welding has been shown to be a viable option among all of the fusion methods tested. The intermolecular interaction between the thermoplastics induced by ultrasonic vibrations causes intermolecular diffusion and trapping of the molecular chain within the liquid state on the interfaces of the weld polymer in this approach, which is a distinguishing property [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…10 Madhukar et al 11 fabricated an AA7150-1% SiCp nanocomposite using ultrasonication assisted stir casting technique and found enhancement of mechanical properties such as tensile strength by 5.42%, microhardness by 7.73% and the porosity reduced to 64.7%. Farshbaf Zinati 12 fabricated a polyamide 6 composite reinforced with multi-walled carbon nanotubes using UAFSP and studied effect of traverse speed on the fabrication and hardness. It was found that the nano-composite are fabricated at higher traverse speeds with effecting the hardness and homogeneity in the composite.…”
Section: Introductionmentioning
confidence: 99%
“…Both physical and chemical approaches have been explored in an attempt to solve the dispersion problem of CNTs in the matrix. The physical approaches include, such as ultrasonic processing , ball milling , and the noncovalent surface modification . Moreover, the chemical modification is also an effective way to improve the dispersion of CNTs .…”
Section: Introductionmentioning
confidence: 99%